The Ethnobotany Study of The Foodstuffs by Local Communities in The Bulumario Village, North Sumatera - Silalahi, Marina; Asmara, Khairissa Trisliani; Nisyawati, Nisyawati (Jurnal Biodjati, 2021)
Food is aÂ primary human need. Various foodsÂ are initially obtained from plantÂ species. Village people have used various food plants based on local knowledge and belief.Â The aimsÂ of this research were to elucidate (1) various food plants traditionally utilization by local people of the Bulumario Village, North Sumatra; (2) plant organs of food plantsÂ that are traditionally used by the local people of Bulumario village. The method used in this study was qualitative. Data were collected through surveys, interviews,Â and participatory observation. A total of 46 respondents were interviewed consisting of 22 men and 24 women who determined by purposive sampling.Â Data were analyzed was descriptively using descriptive statistics. A total of 83 species belonging to 66 genera and 36 families have been used by local communities in Bulumario village as foodstuffs. Those used as a source of carbohydrates (7 species), fruit sources (15 species), vegetables (32 species), and spices (21 species). BasedÂ on plantÂ part used, the foodstuffs are fruit (34 species), leaves (21 species),Â and stems (13 species). Â The composition of food plants are cultivated (53 species), wild (18 species),Â and semi-cultivated (12 species). Solanum torvum, Garcinia attrovidis, Etlingera elatior, and Zanthoxylum acanthopodium are spices especially in Bulumario Village which have bioactivity as an antimicrobial so they are potential to be developed as a natural preservative. Pakkat (Calamus hookerianus, Calamus metzianus, Calamus thwaitesii and Plectocomiopsis geminiflora) have the potential to be developed as a vegetable or carbohydrate source.